Criminal Procedures on Online Application During Covid-19 Pandemic - Ferdian Togi Sinurat; Markoni Markoni; Wasis Susetio (Penerbit Kemala Indonesia, 2021)
The spread of the Covid-19 (Corona Virus Disease-2019) outbreak has paralyzed community activities in the various aspects. Here, the field of law itself, spread of Covid-19 was greatly influenced the course of the law enforcement process. The trial activities that were most affected by the problem due to the Covid-19 pandemic, namely in criminal proceedings. This study uses a comparative approach supported by literature study. This study aims to determine the comparison of the application of online and offline criminal trials in Indonesia and other countries, especially in the United States. Online criminal trial in Indonesia is regulated in PERMA No. 4 of 2020, while in the United States it is regulated in the CARES Act and many things arise from the application of online criminal proceedings, in Indonesia, including inconsistencies in the Criminal Procedure Code with, legality of the proof system, psychological impact on the parties, also technological constraints as a new breakthrough. Based on the theory of justice, the legal certainty, and comparative benefits of online criminal justice (e-courts / e-litigation) and offline criminal justice should be done offline because it fulfils the theory of justice and legal certainty. In this study, we also obtain the strengths and weaknesses to compare, the results whether the application of the online criminal trial is effective and efficient.